An Analysis of Determinants Affecting the Returns of Dow Jones Sustainability Index United States - Pitoska, Electra; Katarachia, Androniki; Giannarakis, Grigoris; Tsilikas, Charalampos (International Journal of Economics and Financial Issues, 2017)
During the last decades there has been an increased interest regarding socially responsible stock indexes. However, there is a limitless literature body regarding the factors that affect these types of indexes. For this reason, this paper intends to investigate whether consumer sentiment, US dollar value to major currencies and Gold prices affecting the returns of Dow Jones Sustainability Index (DJSI) US from September 1999 to September 2016 using monthly data. The generalized autoregressive conditional heteroskedasticity model is used and revealed that consumer sentiment affect positively the DJSI US, while Gold prices and the US dollar value have a negative effect on it. The results of this study add to the international literature by providing important implications for investors and policy makers along with business manager forecasting and planning. Keywords: Dow Jones Sustainability Index, Consumer Sentiment, Gold, US dollar, GARCH model JEL Classifications: C58, Q40, Q50, M21